Health Services Economy and its Impact on Economic Growth in Sudan - Mohamed, Khaled Abdel Aziz Hassan (Journal of Economic, Administrative and Legal Sciences, 2018)
This study examines the impact of health service economics in relation to economic growth in Sudan. It explains the concept of health service economics, and the demand for the good performance of health services, as a factor effecting economic growth rates. The study also details the development of the health sector in Sudan, focusing on the role of medical staff working in the health field. The study also discusses health facilities in Sudan, describing how their development aligns with population growth, improved GDP, and the overall growth rate of the economy, in addition to per capita GDP. The study identifies a shortfall in the provision of health services in Sudan, due to the migration of medical personnel, as well as inadequacies in terms of the number of health facilities available. It notes that these insufficiencies influence the delivery of health care services to the population, leading to low economic growth rates resulting from restricted productivity. In conclusion, the study recommends the allocation of higher budgets to the health sector to improve health facilities and boost medical staff numbers, on the premise that the development of the health sector will support economic development overall.